Genetic diversity and disease susceptibility. - Bodmer, W (1997)
The range of genetic diversity within human populations is enormous. Genetic susceptibility to common chronic disease is a significant part of this genetic diversity, which also includes a variety of rare clear-cut inherited diseases. Modern DNA-based genomic analysis can now routinely lead to the identification of genes involved in disease susceptibility, provides the basis for genetic counselling in affected families, and more widely for a genetically targeted approach to disease prevention. This naturally raises problems concerning the use of information on an individual's decisions, but for employment, and health and life insurance.